Dislocation following total hip arthroplasty using dual mobility acetabular components: a systematic review. Issue 1 (January 2017) - De Martino, I.; D'Apolito, R.; Soranoglou, V. G.; Poultsides, L. A.; Sculco, P. K.; Sculco, T. P.
Abstract : Aims: The aim of this systematic review was to report the rate of dislocation following the use of dual mobility (DM) acetabular components in primary and revision total hip arthroplasty (THA). Materials and Methods: A systematic review of the literature according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines was performed. A comprehensive search of Pubmed/Medline, Cochrane Library and Embase (Scopus) was conducted for English articles between January 1974 and March 2016 using various combinations of the keywords "dual mobility", "dual-mobility", "tripolar", "double-mobility", "double mobility", "hip", "cup", "socket". The following data were extracted by two investigators independently: demographics, whether the operation was a primary or revision THA, length of follow-up, the design of the components, diameter of the femoral head, and type of fixation of the acetabular component. Results: In all, 59 articles met our inclusion criteria. These included a total of 17 908 THAs which were divided into two groups: studies dealing with DM components in primary THA and those dealing with these components in revision THA. The mean rate of dislocation was 0.9% in the primary THA group, and 3.0% in the revision THA group. The mean rate of intraprosthetic dislocation was 0.7% in primary and 1.3% in revision THAs. Conclusion: Based on the current data, the use of DM acetabular components are effective in minimising the risk of instability after both primary and revision THA. This benefit must be balanced against continuing concerns about the additional modularity, and the new mode of failure of intraprosthetic dislocation. Longer term studies are needed to assess the function of these newer materials compared with previous generations. Cite this article: Bone Joint J 2017;99-B(1 Supple A):18–24.